Fortschritte in der Thrombozytenfunktionsdiagnostik - Mani, H.; Wolf, Z.; Lindhoff-Last, E. (Hämostaseologie, 2010)
Both for diagnosis of congenital and acquired platelet dysfunction as well as for therapy monitoring after application of platelet function inhibitors various methods have been established for evaluation of platelet function. In contrast to the gold standard of platelet function testing, the light transmission aggregometry in platelet rich plasma the Point-of-care (POC) analyzers allow fast analysis of platelet function without extensive laboratory work up. The conditions of the pre-analytical phase, however, are still of enormous importance in the prevention of medical errors. There is increasing clinical data in monitoring the effect of platelet aggregation inhibitors, showing that quantitative determination of the platelet function degree correlates with risk of increased bleeding or stent thrombosis. However, it is still unclear, which is the optimal test system, to predict the clinical outcome of these patients.
Keywords: Platelet dysfunction; monitoring of platelet function; pre-analytic; POC systems